Caracterização da madeira da metade superior do tronco de árvores de Eucalyptus grandis x Eucalyptus urophylla de 13 anos para produção de celulose - Boa, Ana Carolina (2014)
The eucalypt wood is an important source of raw material for the forest industry, and several studies have been conducted with the objective of adding more quality to this material. The general objective of this research was to evaluate if the wood of the upper trunk of trees 13 years old of hybrid Eucalyptus grandis x Eucalyptus urophylla has the quality required for pulpwood production. Was evaluated the wood properties of four trees of each of the nine clones studied. Two of the clones were from commercial plantations with five years old, located in the town of Aracruz in Espirito Santo State, exclusive to cellulose production. The seven other clones were from plantations 13 years old, located in the town of Alcobaça in Bahia State, for the joint production of lumber and pulp. The results of anatomical, chemical and basic and apparent wood density characterizations were compared, and by the results we found differences between the wood of five years old trees and the upper trunk of 13 years old. The use of statistical multivariate analysis techniques identified that among the clones of the same age there was no variability in the wood properties that distributed them into different groups. Thus, it was possible to infer that there were differences between wood from trees of different ages, but not of the same age. When were evaluated the wood properties of trees with five years old and the upper trunk of 13 years old, it was observed that the upper trunk showed more availability of raw material, due to the higher volume of wood and basic density, addition of fibers with thicker walls and smaller content of lignin.